A Grammatical Cohesion Analysis in the News Discourse: A Case of Russia-Ukraine War - Dhea Syahzana Sahreebanu; Zainur Rofiq (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This paper examines how the use of grammatical cohesion contributes to the coherent of the news discourse in The Jakarta Post reporting on the war between Russia and Ukraine. It identifies and analyzes grammatical cohesion, specifically reference, substitution, and ellipsis, which exist in the news text to bring coherence in the news text. The results revealed the most dominant type of references applied in the text were anaphoric references, and these references are very important to ensure the integrity and readability of the text. The study therefore reveals a lack of substitution because there is the need for precision in war reporting. The insights gained contribute to a deeper understanding of how linguistic devices are employed in the media to build cohesive and coherent narratives, offering valuable implications for both discourse analysis and English language education.